Pulse dose of oral itraconazole is effective in the treatment of onychomycosis - Ahmed, Afrin; Ali, Eakub; Khondker, Lubna; Khan, Md Shirajul Islam (Journal of Pakistan Association of Dermatologists, 2016)
Background Onychomycosis is a recalcitrant disease of the nails caused by dermatophytes, yeasts, and molds. Â Objective To see the efficacy of pulse dose of oral itraconazole in the treatment of onychomycosis. Â Patients and methods It was an open clinical trial which was carried out for a period of 2 years from March 2009 to February 2011, in the outpatient department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka. Bangladesh. Thirty patients with onychomycosis were recruited purposively. 30 patients of onychomycosis were treated with oral itraconazole 400 mg/day, seven days a month for three months. Â Results Mean age of the respondents was 36.57Â±14.01 years and male to female ratio was 1:1. Among the patients, 36.7% cases had involvement of toenails and 63.3% cases had involvement of fingernails. In 6.7% cases onychomycosis was mild, 80.0% cases moderate and in 13.3% cases severe. Three months after treatment with itraconazole, improvement was found in 66.7% cases and marked improvement in 33.3%. Before treatment, culture was found positive in 30% cases and three months after treatment, culture became negative in 66.7% cases. Â Conclusions Monthly one week cycle of oral itraconazole 400 mg daily for 3 months is effective therapeutic option for onychomycosis. Â